Liquid Chromatographic Tandem Mass Spectrometric (LC-MS/MS) Determination of Perfluorooctane Sulfonate (PFOS) and Perfluorooctanoic Acid (PFOA) in the Yolk of Poultry Eggs in Malaysia - Tahziz, Atiqah; Haron, Didi Erwandi Mohamad; Aziz, Mohd Yusmaidie (MDPI, 2020)
Perfluorooctane sulfonate (PFOS) and perfluorooctanoic acid (PFOA) are widely used in products, and are known for their water and grease repellent properties. The persistence nature and potential toxicity of these substances have raised substantial concerns about health effects. Regarding humans, food consumption has reportedly been a significant source of exposure for both compounds. Hence, this study was performed to develop and validate an analytical method for PFOS and PFOA in egg yolks using liquid chromatographic tandem mass spectrometry (LC-MS/MS) followed by the determination of concentration of both compounds in the yolk of poultry eggs in Malaysia. A total of 47 poultry egg yolk samples were extracted by a simple protein precipitation technique using acetonitrile. The analytical method was developed using LC-MS/MS and validated based on the Food and Drug Administration (FDA)’s Bioanalytical Method Validation guidelines. The results revealed that PFOS was quantitatively detected in six samples, with the concentration range between 0.5 and 1.01 ng g−1. Among these, five samples were from home-produced chicken eggs, and one sample was from a quail egg. The levels of PFOA in all samples were below the quantifiable limit (<0.1 ng g−1). This indicated that the contamination of PFCs in poultry eggs were mostly attributed to the nature of free foraging animals, which had direct contact with the contaminants in soil and feed. In conclusion, a fast and robust analytical method for analyzing PFOS and PFOA in egg yolk samples using LC-MS/MS was successfully developed and validated. The presence of these emerging contaminants in this study signified widespread pollution in the environment. © 2020 by the authors.